2010
DOI: 10.1007/s11239-010-0473-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation in the hospital: analysis of patients at risk

Abstract: Warfarin is one of the most commonly used medications associated with adverse events. Warfarin therapy is often initiated or continued in the hospital, yet hospitalization increases the risk of poor anticoagulation control with warfarin. To help understand this, we retrospectively reviewed the records of patients admitted to our hospital during a 6-month period who were given at least one dose of warfarin. To explore factors that may have contributed to poor anticoagulation control, we compared characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
1
11
0
2
Order By: Relevance
“…Moreover, this study showed that our inpatient detailed dosing protocol reduced the number of patients with INR higher than 5, a level that has been shown to be associated with increased risk and complications [4]. This result is even more notable considering that the intervention patients were more likely to be receiving antibiotics, which have been shown to interact with warfarin and increase the risk of levels out of the therapeutic range [3].…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Moreover, this study showed that our inpatient detailed dosing protocol reduced the number of patients with INR higher than 5, a level that has been shown to be associated with increased risk and complications [4]. This result is even more notable considering that the intervention patients were more likely to be receiving antibiotics, which have been shown to interact with warfarin and increase the risk of levels out of the therapeutic range [3].…”
Section: Discussionmentioning
confidence: 67%
“…Prior studies have shown that poor monitoring can worsen control [3]. Even if this lack of monitoring is a contributing factor for poor control, the dosing protocol allows this oversight using existing pharmacy resources, which is an advantage to hospitals in the face of rising costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations